Persepsi Wisatawan Mancanegara terhadap Kunjungan Ekowisata di Bukit Lawang - Yana Charolin, Helen Eli (Tourism, Hospitality And Culture Insights Journal, 2024)
Bukit Lawang ecotourism offers millions of charms through natural scenery, flora and fauna that live in the nature reserve. Sumatran orangutans are an icon of foreign tourists visiting Bukit Lawang. Sumatran orangutans have become an icon for foreign tourists visiting Bukit Lawang. This study aims to analyze the perception and satisfaction of foreign tourists when visiting Bukit Lawang. This research method uses quantitative descriptive methods by using questionnaires as a tool to measure tourist perceptions. The characteristics of foreign tourists in this study are mostly men, aged 29 to 34 years, come from Korea, have a visit duration of 2 to 3 days, first visit, and are ready to return. Tourist perceptions are divided into several categories, including Activities that are in great demand by tourists such as enjoying the beauty of nature and tracking. Regarding facility preferences, foreign tourists are satisfied with the facilities provided. Travellers' perceptions of accessibility and networking are rated good.